Coexpression Analysis Reveals Dynamic Modules Regulating the Growth and Development of Cirri in the Rattans (Calamus simplicifolius and Daemonorops jenkinsiana) - Wang, Jiongliang; Ma, Xuelian; Yang, Jiaotong; Hui, Yanan; She, Jiajie; Tian, Tian; Li, Zhongqiu; Xu, Wenying; Gao, Zhimin; Su, Zhen; Zhao, Hansheng (Frontiers in Genetics, 2020)
Rattan is being regarded as one of the major non-timber forest products only second to wood and bamboo on the world. Though two released genomes of Calamus simplicifolius and Daemonorops jenkinsiana facilitate the genome-wide gene function analyses, the co-expression networks contributes to providing more comprehensive and complete annotations of gene function at the transcriptome level. We thus rendered the analysis of co-expression networks for the two rattans (Calamus simplicifolius and Daemonorops jenkinsiana) through integrating genome sequences, in-house transcriptome data from different development stages of cirrus and a well-developed strategy. The result showed 3,504 and 3,027 functional modules were respectively identified in Calamus simplicifolius and Daemonorops jenkinsiana based on a combination of co-expression networks, gene families classification and function enrichment tools. The modules covered the major developmental processes, including photosynthesis, lignin biosynthetic process, flavonoids biosynthesis and phenylpropanoid biosynthesis. Reference annotations were refined by the co-expression networks and functional modules. Additionally, we yielded novel insights into the regulation of cirrus growth and development in rattans, suggesting the flavonoids biosynthesis pathway may be superiority compared to the lignin biosynthesis pathway in the formation of rattan cirrus. Furthermore, Rattan-NET (http://rattan.bamboogdb.org/), an online database containing the analysis tools of Gene Sets Enrichment Analysis, Module Enrichment and Cis-element analysis were constructed for the easy analysis of gene functions and regulation modules involved in the cirrus growth and development of cirrus in the rattans.